Post-program impacts of transfer programs on child development: Experimental evidence from Bangladesh - Ahmed, Akhter; Hamadani, Jena Derakhshani; Hassan, Md. Zahidul; Hidrobo, Melissa; Hoddinott, John F.; Koch, Bastien; Raghunathan, Kalyani; Roy, Shalini (International Food Policy Research Institute, 2021)
Evidence shows transfer programs can improve early childhood development (ECD). However, knowledge gaps remain on how short-term impacts on ECD evolve as children grow older, how program design features and context affect child development impacts over time, and through what pathways such impacts occur. We study the Transfer Modality Research Initiative (TMRI), a 2-year randomized controlled trial in two regions of Bangladesh that provided cash or food transfers, with or without complementary nutrition programming, to mothers of children aged 0-2 years at baseline. Drawing on data collected at 6 months post-program (when children were about 2-4 years old) and at 4 years post-program (when children were about 6-8 years old), we assess post-program impacts of TMRI on children’s home environment and development. We find strong post-program impacts on the home environment from cash transfers in the Northern region, particularly when combined with complementary programming, however limited post-program effects on child development outcomes. Improvements found in child development tend to be concentrated in boys. We find few post-program improvements in home environment or child development from food transfers in the Southern region, with or without complementary programming.